Percurso dos gêneros do narrar no ensino de língua materna : um diagnóstico com foco nos alunos - Cardoso, Maísa (2009)
Despite narration is an ability developed in childhood, prior to school phase, various academic works have shown the increasing students' apathy in reading and text production in narrative genres. Bearing such contradiction in mind, this research aims to outline, from the student perspective, the course of narrative text in Portuguese Language classes of Basic Education and its repercussion in extra class activities. The research context is grounded in primary and secondary school in the region of Maringá, from where the data were collected by means of questionnaires with students from the fifth and eighth grades of primary school, and third grade of secondary school. This investigation draws on an interactionist perspective, on Bakhtin's concept of genre (BAKHTIN, 2003), and on Adam's concept of typology (apud Bronckart, 1999; Brandão, 2000; Bonini 2005). We adopted the model of genre grouping proposed by Dolz e Schneuwly (2004), and we highlighted two narrative type concepts: the first one includes the genre of reporting (Dolz e Schneuwly, 2004), characterized by the sequence of events, situated in time, but without conflict or aesthetic treatment; the second one concerns itself with the sequence of events, fundamentally marked by the presence of conflict and by an artistic work with the word. The genres aforementioned belong exclusively to the order of narration (Dolz e Schneuwly, 2004). It is in the latter concept that this study is grounded in, due to the relevance of approaching literary narrative genres in the classroom, and the role of literature in men's education (CANDIDO, 1972). The research looks at checking: a) if the students recognize a narrative text and are able to point out its characteristics and main elements; b) if the students like reading and produce/reproduce narrative texts; c) if the school, throughout grades, changes to second plan the work with narrative texts; d) if the students read and write narrative texts outside school by their own initiative. Data analysis showed that the students were more apt to recognize a narrative Type - in its wider concept - as compared to the various narrative genres (literary). Their recognition capacity improves throughout their school life. As regards pleasure in reading, the students showed to like reading better than producing narrative genres at school, which in turn gradually replaces the reading of narrative genres by others, especially the argumentative type ones. In this respect, it is in the fifth grade that the study of narratives predominates; the eighth grade is concerned with argumentative texts, whose predominance is intensified in secondary school, in which the reading and the narrative analysis are restricted to the exam of vestibular. Outside classroom, the students stated to prefer reading, mainly the narrative genres, highlighting comedy, action, thriller and adventure. As regards production, in school context, the genres which emerged in all grades were the narration, dissertation, summary, traditional school texts whose approach is not connected with the conditions of textual production. It is possible to notice that in initial grades, other genres are added to the aforementioned ones, which characterizes a major textual diversity. However, the extra class production contemplates texts of the narration and reporting order, in blogs and diaries, with a determined interlocutor and a proper style. The students reported having had experiences with oral narratives in childhood and showed pleasure in telling stories, jokes, cases and other forms of oral narrative outside school. The final conclusion is that, even when leaving school, narrative remains in the student life.